Statistical Analysis of Football Players’ Performance - Kanišauskienė, Karolina; Veličkaitė, Simona (Jaunųjų mokslininkų darbai, 2019)
In this paper, we analyze Šiauliai “Gintra-University” football club players’ physical fitness test data and match reports for 2016. The aim of the study is to present a statistical survey on the football players’ performance. One of the tasks was to assess “Gintra-University” team players’ physical fitness tests and compare them to fitness standards for women admitted to the police school. After checking the hypothesis that the average score is the sum of scores divided by the total number of matches it was found that the team players were assessed satisfactorily. Linear regression model was done to predict time spent on a football field, and logistic regression model - to predict the probability that a randomly selected team player will score a goal.